1996
DOI: 10.3109/00016359609003528
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride release and uptake in vitro from a composite resin and two orthodontic adhesives

Abstract: The aim of this study was to investigate the fluoride release and uptake characteristics of a composite resin (Tetric) and two orthodontic adhesives (VP 862 and Saga Bond), with a type-II glass ionomer cement (Ketac Fil) as a control. Test specimens in 2 ml deionized water released fluoride over a period of 33 days. Ketac Fil released 54 and 15 times more fluoride than Tetric after 24 h and 1 month, respectively, whereas the two adhesives released amounts between these values. Specimen exposure to 1000-ppm NaF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 20 publications
1
20
1
Order By: Relevance
“…These low-level concentrations were produced by ytterbium trifluoride which is incorporated into this material and has extremely low solubility. 8,14 The IC method gives meaningful and reproducible measurements of fluoride concentration at the fluoride concentrations above 0.001 ppm, but the data from the ISE method becomes meaningless below 0.1 ppm. 13 Figure 1 The cumulative plots of fluoride release from all materials using the ISE and IC methods.…”
Section: Discussionmentioning
confidence: 99%
“…These low-level concentrations were produced by ytterbium trifluoride which is incorporated into this material and has extremely low solubility. 8,14 The IC method gives meaningful and reproducible measurements of fluoride concentration at the fluoride concentrations above 0.001 ppm, but the data from the ISE method becomes meaningless below 0.1 ppm. 13 Figure 1 The cumulative plots of fluoride release from all materials using the ISE and IC methods.…”
Section: Discussionmentioning
confidence: 99%
“…Studies into the anticariogenic effects of fluoridereleasing restorative materials have shown that fluoride is released from glass-ionomer cements [14][15][16][17][18][19][20] , resin modified glass-ionomer cements [17][18][19][20][21] and resin composite [20][21][22][23][24][25] . According to studies comparing the fluoride release and recharge properties of conventional glass ionomers and more recently developed fluoride-containing resin composite [20][21][22][23][24][25] , the amount of fluoride released from both these restorative materials was high during the first few days after immersion in DW, but dropped immediately thereafter [19][20][21] . In addition, Xu et al 18) reported that fluoride releasing ability could be restored by applying topical fluoride, and that materials with a high initial fluoride release rate Table 3 Amount of fluoride release in phase 3…”
Section: Discussionmentioning
confidence: 99%
“…Conventional resin-based sealant normally does not demonstrate fluoride recharge as demonstrated by our control group results 6,7) . However, some studies found that resin-based materials can recharge low amounts of fluoride 23,24) . Fluoride in the surrounding water after recharge is probably due to the release of surface-retained fluoride, rather than fluoride being incorporated into the sealant 24) .…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies found that resin-based materials can recharge low amounts of fluoride 23,24) . Fluoride in the surrounding water after recharge is probably due to the release of surface-retained fluoride, rather than fluoride being incorporated into the sealant 24) . The different findings from our study and other studies may result from different methods of rinsing and cleaning the material in water after fluoride recharge.…”
Section: Discussionmentioning
confidence: 99%